Petersen Family Host Private Reception for Mayor of Djambul - Watkins, Howard::::::::: (1989)
?, Ken Clarke, ?, Mayor of Djambul speaking, Chris Petersen, Karen Humphrey, Walt Loscutoff, 2 guests, Susan Loscutoff and 2 guests